Digital Financial Literacy Learning in Shaping Non-Cash Transaction Behavior of Upper Secondary School Students - Asfin Herianto; Jumaenia Jumaenia (Civiliza Publishing, Indonesia., 2026)
The development of information and communication technology has encouraged the increasing use of digital money as a means of transaction, especially among the younger generation. This study aims to analyze the behavior of digital money usage among students of SMAN 1 Wangi-Wangi, Wakatobi Regency and identify the factors that influence it and its impact on students' financial behavior. This research method uses a quantitative approach with a survey method of 42 grade XII students as respondents. Data were collected through a Likert-scale questionnaire and analyzed using validity tests, reliability tests, descriptive statistics, normality tests, and simple linear regression analysis. The results showed that 64.3% of students had used digital money, with the Dana application as the most widely used service. Validity and reliability tests showed that the research instrument was valid and reliable with a Cronbach's Alpha value of 0.866. Regression analysis showed that the use of digital money has a positive and significant effect on students' digital money usage behavior (t = 5.418; sig. = 0.000). The use of digital currency has positive impacts such as ease of transactions, increased financial technology literacy, and ease of financial management. However, it also has the potential for negative impacts such as consumer behavior, technological dependency, and reduced spending control. Therefore, improving financial literacy and monitoring the use of digital currency are essential to ensure students utilize this technology wisely and responsibly.